On Security Notions of Steganographic Systems - CHANG, Kisik (Institutional Knowledge at Singapore Management University, 2005)
We define the notion of pseudoprocessingness to formulate chosen-input-attack, chosen-stego-attack, and key-recovery. We then construct a efficient, provable secure steganographic algorithm against chosen-input-attack and key-recovery. So far as we know, this is the first paper dealing with those security notions.